Antarctic Bottom Water Jets Flowing from the Vema Channel - Eugene G. Morozov; Oleg A. Zuev; Dmitry I. Frey; Viktor A. Krechik (Water, 2022)
Properties of the abyssal current of Antarctic Bottom Water (AABW) from the Vema Channel are studied based on temperature, salinity, and velocity profiler (CTD/LADCP) data. Previous studies over a period of almost 30 years revealed that very intense current of AABW exists in the Vema Channel. Later, it was found that this current consists of two branches. One branch spreads over the bottom of the channel; the other branch is elevated over the western wall of the channel. The deepest branch decays after it passes approximately 100 km while the upper one continues further to the North Atlantic and is the source of abyssal waters in the Canary and Cabo Verde basins of the North Atlantic. Data analysis suggested that the upper jet splits into two. One of these descends down a canyon at 24°30′ S, while the other (the third one) remains on the continental slope, and indications of its existence are also found at 24°00′ S. This research analyzes the existence and pathway of this third branch that can be traced up to latitude 24° S. Velocity measurements in 2022 allowed us to confirm the existence of this third branch.